Impact of Meat Processing on DNA Quantity, Purity, and Integrity in Commercial Pork Products Assessed by TaqMan qPCR - Abinawanto; Rahayu, Ernawati Puji (Universitas Muhammadiyah Surakarta, 2025)
TaqMan qPCR analysis for detecting adulteration in processed meat products requires DNA with a high quantity, purity, and integrity. This study aims to evaluate the quantity, purity, and DNA integrity of various commercial pork products focusing on their ability to amplify the Cyt b gene. Fresh pork was used as a positive control, while five processed products - jerky, floss, meatball, canned corned, and smoked pork - were extracted for analysis. The DNA concentration and purity then measured, visualized using gel electrophoresis, and subjected to qPCR amplification. Statistical analysis of DNA concentration, purity, and ct value was carried out using one-way ANOVA followed by the Tukey post hoc test. The results showed significant differences in concentration, purity, and Ct values between all samples and positive controls (P˂0.05). Meanwhile, the Tukey test showed that all samples and fresh pork concentration differed significantly (P˃0.05) except between canned corned and fresh pork (P˂0.05). The purity was significantly different between the positive controls with pork meatball and smoked pork (P˂0.05), while the Ct​ value of all samples and positive controls were significantly different (P˂0.05) except for fresh pork and jerky (P˃0.05). All the commercially processed products experienced DNA fragmentation. Meat processing affects DNA concentration, purity, genomic integrity, and the amplification ability of qPCR.